Hemorrhagic viral encephalitis: an unusual presentation of chikungunya viral infection - Kamble, Aarav S.; Kute, Akshay P.; S., Anitha M.; Badadhe, Pooja (International Journal of Research in Medical Sciences, 2024)
Chikungunya is a mosquito borne alpha virus that is implicated in causation of viral fever with arthralgia which is literally translated as “to become contorted” depicting the severity of the pain. The infection in itself is self-limiting, however the joint pain and myalgia associated with it might linger till weeks, months or even years. Some cases also progress to the viral fever associated complications such as meningitis, encephalitis and Guillain–Barré syndrome. Though, some cases of encephalitis have been reported, it is a relatively rare complication. Here we present a case of a 17 years old male with viral fever secondary to Chikungunya infection which progressed to hemorrhagic encephalitis which is relatively unknown and rare complication of the infection.